Characteristics of sediment pollution study with trace elements in the Kufa River, Iraq - Ali Kareem Jasim (EQA)
The deterioration of water quality due to increasing industrial and urban activities poses a growing threat to riverine ecosystems. Sediments, acting as both carriers and sinks for contaminants, are critical in evaluating environmental pollution and identifying its potential sources. This study investigates the concentrations and spatial distribution of selected heavy metals (Cd, Pb, Zn, Cu, Ni) in the bottom sediments of the Kufa River, located in Najaf Governorate, Iraq. Fine sediment fractions (<0.02 mm) were analyzed using the Geoaccumulation Index (I-geo) to assess pollution levels. The findings indicate that heavy metal concentrations were generally low and spatially homogeneous across the three selected sites. Most metals fell within the "unpolluted" to "moderately polluted" categories according to the I-geo classification. Nickel exhibited slightly elevated values at some sites, suggesting localized influence. Areas with low hydrodynamic activity showed marginally higher concentrations due to potential accumulation. These results provide a baseline understanding of heavy metal behavior in the Kufa River and highlight the importance of continuous sediment monitoring. The study supports the development of long-term environmental management strategies to preserve river health and prevent future degradation.